Losers' and Non-voters' Consent: Democratic Satisfaction in the 2009 and 2013 Elections in Germany. Issue 3 (9th September 2016) - Rich, Timothy; Treece, Mallory
Abstract : The literature on losers' consent identifies clear distinctions in perceptions of democracy between electoral losers and winners. However, little of the literature addresses the complexities of mixed member electoral systems or compares this winner–loser divergence to that of non-voters. An analysis of post-election surveys in Germany in 2009 and 2013 allows for a disaggregation of types of losers and non-voters. Results find that voting for a district candidate from a losing party has a greater effect on perceptions than voting for a losing party in the proportional representation tier, while losing in both appeared to slow the decline in positive evaluations of the system. Meanwhile clear distinctions between perceptions of different types of non-voters emerge.